Poética y orden editorial de los Romances de Lorenzo de Sepúlveda - Ventura Escudero, Luis Carlos (El Colegio de México, 2023)
The loss of the princeps edition of the Romances of Lorenzo de Sepulveda has left us with interesting questions about its conformation. Even though we have editions close to it and clues about contemporary editorial practices, we don’t have a clear idea as to the order that the first edition, printed in Seville, must have followed. A study of Sepulveda’s poetics and of his views on the ways to read the Romancero ─whether as narrative cycles or following the variatio paradigm─ can shed light on the problem and bring us closer to the order of the original edition.